TINGKAT KEMAMPUAN PUKULAN SERVICE PENDEK BACKHAND DAN PUKULAN FOREHAND BULUTANGKIS MAHASISWA PJKR UNUGIRI - Apriyanto, Rohmad; Fahrudi, Ahmad; S., Adi; Aliriad, Hilmy; Da'i, Mohamad (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2024)
The purpose of this study is to determine the level of ability of service punches andbadminton forehand punches of PJKR unugiri class 2020 A students that the skill of service punches and forehand punches of PJKR Unugiri class 2020 A students has a good level of ability. The method used in this research is a quantitative descriptive method with researchinstruments of service punches and badminton forehand punches, demgam the number ofresearch samples as many as 29 students of class 2020 A, The data analysis technique used in this study is descriptive statistics with a percentage formula.The results of the service punch research there are 11 students with a percentage of 40%have good skills and 30% have a very good level of ability, As for the forehand punch,there are 8 students with a percentage of 35% having a very good and good level of ability.